Optimizing Agricultural Supply Chain Transparency in Indonesia through Blockchain and Smart Contracts - Konita Lutfiyah; Harlis Setiyowati; Cicilia S Bangun; Amroni; Carlos Perez (IAIC Bangun Bangsa, 2025)
This research explores the integration of blockchain technology within Smart Farming 4.0 to improve efficiency, transparency, and sustainability in Indonesia’s agricultural sector. the challenge of transforming traditional agriculture into a modern, data-driven system remains significant, especially for smallholder farmers. By leveraging blockchain, the Internet of Things (IoT), and Artificial Intelligence (AI), In this study, investigates how these technologies can opti- mize supply chains, enhance product traceability, and reduce distribution costs. Employing a mixed-method approach, data were collected through interviews with farmers utilizing blockchain-based systems and surveys targeting milenial farmers. The findings reveal that blockchain significantly improves trace- ability and logistics efficiency, while highlighting key barriers such as low digital literacy and limited access to technology. The results emphasize the importance of government and private sector collaboration in providing incentives, digital literacy training, and infrastructure support. Ultimately, the study offers practical insights into accelerating digital transformation in agriculture and promoting sustainable food systems through technological innovation.